Monitoring Carbon Storages of Plantation Forests in Reclaimed Land and Natural Forests in Zinc and Coal Mines, Northern Thailand - Suppagarn Thiteja (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The research aims to monitoring carbon storages of plantation forests in reclaimed land and natural forests in Phadeng zinc mine (Mae Toa Watershed, Maesod district, Tak province) and Banpu coal mine (Li district, Lamphun province) Phadeng zinc mine was operated in the right upper Mae Tao watershed and thus affected land use in the watershed. The research composed of three parts: (1) Land use change in watershed (2) survey of plant community and carbon storage in forest plantations in two areas, plantations in degraded forest for compensated in mine land and plantations in dumping area, and (3) studying growth, production and carbon storage of tree species planted around office areas. The land use changes in Mae Tao watershed was divided into 4 periods according to mining: (1) pre-mining (period I), (2) during mining as before forest plantation (period II) (3) during mining as after forest plantation (period III), and (4) post-mining (period IV). The methods included field survey and remote sensing technology for classifying types of land use. The results showed percentage proportions of natural forest to the lower watershed having mining in the four periods were 73.3, 63.6, 41.4 and 35.9, respectively. Other land use had different values: agricultural land = 25.7, 29.8, 15.9 and 17.2; mineland = 1.0, 6.6, 14.3 and 1.3; and plantation forest = 0, 0, 18.3 and 45.6. Agriculture was changed from for subsistence to commercial purpose. Natural forest was decreased progressively caused by mainly forest clearing for cultivation. Forest plantation in mine land, adjacent degraded forest land and bare forest land taken from the farmers increased the forest area proportion in the watershed, from 73.3% (period 1) to 81.5% (period 4). Carbon storage in Phadeng zinc mine area was studied into five areas: (1, 2) the restoration plantation forests included 19- and 20-year old stands (PF1; 5 plots, PF2; 5 plots), (3) the reclamation dumping area plantation forests 9 to 19 year-old (PF3; 3 plots), (4) the dry dipterocarp forest (DDF; 5 plots) and the mixed deciduous forest (MDF; 5 plots) The plots each, 40x40 m2 in size were used for plant survey in the forests. Plant data were collected by measuring stem girth at 1.3 m above-ground and tree height of all tree species with the height over 1.5 m. Carbon storage (CS) in biomass was measured using allometric equations. The result showed the average of the CS in the plantation forest: PF1, PF2 and PF3 were 40.5, 57.5 and 36.4 Mg ha-1, respectively. The CS of natural forest: DDF and MDF were 94.5 and 147.0 ha-1, respectively. The relationship between the above-ground carbon storage (ACS) and NDVI values based on Lansat-8 satellite imagery was investigated in different season during a year, and found that the data in December were the most corelated values to the ACS of PF1, PF2 and MDF, the data in January was the most corelated values to the ACS of DDF and the data in May were the most corelated values to the ACS of PF3 Banpu coal mine was operated in the national reserved forest nearby Ban Hong village. The research composed of two parts: (1) survey of plant community and carbon storage in natural forest (Dry dipterocarp forest) which is the community forest, and (2) studying growth, production and carbon storage of forest plantation in dumping areas. Land use change was not investigated in this area. Carbon storage in Banpu coal mine area field vegetation survey was done in the 18-year-old plantation forests in dumping area; PF4 and adjacent the dry dipterocarp forest; DDF2 using sampling plots, each of size 40×40 m, 12 plots for the PF4 and 10 plots in the DDF2. Plant data were obtained by measuring stem girths and tree heights. Amounts of biomass and carbon storage (CS) were calculated using allometric equations. Relationship between the CS and vegetation index of satellite images was taken from 2015 Landsat image for multiple regression analysis to obtain the best correlation. The equation used to estimate the CS in the PF4 and DDF2 were 43.6 and 56.3 Mg ha-1, respectively. The best equation for estimating the above-ground carbon storage (ACS) in the PF4; ACS = (154NDVI)+(103RVI)-76 (R2 = 0.96) and in the DDF2, ACS = (334NDVI)+(248RVI)-222 (R2 = 0.91). The equation were estimated ACS amounts in PF4: before mining (1987), 81.7 Mg ha-1, during mining (1990, 1995; before plantation ), 0.72 and 10.7 Mg ha-1, respectively and during stand development (1997, 2000, 2005, 2010, 2015, 2016, 2017) were in the following order; 15.2, 25.0, 35.1, 36.8, 41.5, 50.1 and 36.83 Mg ha-1, respectively. After 18 years reforestation, the ACS in biomass of PF4 was increased to 75.55% of adjacent natural forest. The decreased ACS in 2017 was caused by standing dead trees and illegal tree cutting.